The Role of Management Accounting in Supporting Strategic Business Decisions (gjstudies, 2019)
This research presents a novel, cross-disciplinary framework that re-conceptualizesthe role of management accounting from a passive information provider to an active, strategic co-pilot by integrating principles from cybernetic systems theory,behavioral economics, and real-time data analytics. Moving beyond traditionalcost accounting and budgeting, we propose the Strategic Intelligence AccountingSystem (SIAS), a dynamic, feedback-driven model designed to navigate complex,volatile business environments. The core innovation lies in its application of a cybernetic control loop—sensing, interpreting, modeling, and acting—to accountingdata flows, enabling proactive scenario simulation and strategic opportunity identification rather than mere historical reporting. We formulate and address uniqueresearch questions concerning the design of accounting systems that can managestrategic ambiguity, the behavioral impact of accounting information framed asstrategic narratives, and the quantification of strategic flexibility. Our methodology employs a hybrid approach, combining a conceptual design science frameworkwith an agent-based simulation model to test the SIAS in a simulated competitive market environment characterized by information asymmetry and disruptiveshocks. The results demonstrate that organizations utilizing the SIAS frameworkexhibit a 23.7% higher rate of successful strategic adaptation to unforeseen market disruptions and a 31.2% improvement in long-term resource allocation efficiencycompared to those using conventional activity-based costing systems. Furthermore,the simulation reveals a critical, non-linear relationship between the granularity ofmanagement accounting data and strategic decision quality, identifying an optimal’informational sweet spot’ beyond which cognitive overload degrades performance.The study concludes that the future of management accounting is not in moreprecise historical data, but in architecting adaptive, forward-looking informationsystems that explicitly model strategic uncertainty, thereby making a distinct andoriginal contribution to both accounting science and strategic management theory.